The road to Marabar: The caves episode in E. M. Forster’s A Passage to India (1924) - Miguel Alarcão (VIA PANORAMICA: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2025)
Just over one hundred years after the publication of E. M. Forster’s novel A Passage to India (1924) and forty years after the production of David Lean’s eponymous film (1984), besides Santha Rama Rau’s play in the interim (1960), this article focuses on the episode of the trip to the Marabar hills and caves, and, particularly, on the metaphorical or inner “trip” (in)to Adela’s mind, one that invites psychoanalytic approaches and readings. In fact, the coeval connection between the writings of E. M. Forster (1879-1970), Sigmund Freud (1856-1939) and C. G. Jung (1875-1961), set and seen in the larger context of the epistemological relationship(s) between literature and psychoanalysis, has not been, in my view, sufficiently emphasized and explored hitherto.